Aktivitas Antioksidan Ekstrak Etanol Daun Kale Hijau dan Ungu (Brassica oleracea L.) - Umiyuliatul Nurfarida; Martina Kurnia Rohmah; Yani Ambari (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2026)
Kale (Brassica oleracea L.) is a plant from the Brassicaceae family that is often consumed by the public. Kale leaves contain vitamin C, phenolic compounds, and pigments that have the potential as antioxidants. Kale leaves that are often consumed by the public are green kale and purple kale. This study aims to determine the comparison of antioxidants between green kale and purple kale using the DPPH method. Green and purple kale leaf Simplicial powder was macerated using 96% ethanol solvent. The extraction results were then tested qualitatively for their phytochemical content using phytochemical screening. Antioxidant activity was tested qualitatively and quantitatively (DPPH method). The results showed that the antioxidant activity (IC50) of Vitamin C, purple kale, and green kale leaves extract successively are 3.19 µg/ml (very strong), 100.03 µg/ml (strong), and 144,35 µg/ml (moderate). The antioxidant activity of purple kale leaves is stronger than green kale. leaves.